Loss of Arabidopsis ACR11 results in altered C/N balance and high sensitivity to nitrogen toxicity - Kunkel, Jacob R.; Maeda, Hiroshi A.; El-Azaz, Jorge (Frontiers in Plant Science, 2025)
IntroductionPlants invest large amounts of resources to produce the twenty proteinogenic amino acids that are essential for growth. However, we still lack a comprehensive understanding of the regulation of amino acid metabolism during the plant life cycle. Plants have a highly conserved ACT domain repeats (ACR) family proteins, which are structurally similar to the bacterial sensor protein GlnD that regulates a key enzyme for nitrogen assimilation and amino acid biosynthesis, glutamine synthetase (GS). MethodsWe investigated the role of the plastidial ACR proteins acr11 and acr12 in the regulation on amino acid metabolism by quantifying the levels of amino acids and other metabolites in Arabidopsis acr11 and acr12 knockout mutants grown under varying light and nitrogen fertilization conditions.ResultsUnlike acr12 plants, which showed only minor growth alterations, acr11 mutants exhibited markedly delayed growth and carbon/nitrogen imbalance. At the metabolic level, acr11 plants showed overaccumulation of free amino acids and other nitrogen-containing metabolites, particularly when grown under high nitrogen conditions. Further, acr11 plants exhibited a marked decrease in the levels of keto acid intermediates from central carbon metabolism that are precursors to amino acid biosynthesis. Quantification of total GS activity, a potential regulatory target for acr11 according to previous studies, shows similar levels of GS activity between acr11 and Col-0 controls under the growth conditions tested here.ConclusionsOur findings suggest that acr11 is a negative regulator of plant nitrogen metabolism that operates through a mechanism different from bacterial GlnD, possibly regulating other molecular targets besides plastidial GS.